Fibre reinforced concrete and high performance fibre reinforced cementitious composites: An overview - Raman, Sudharshan N.; Mohd. Zamin, Jumaat, Prof. Dr.; Hilmi, Mahmud, Assoc. Prof. Dr.; Muhammad Fauzi, Mohd. Zain, Prof. Dr. (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s homepage at http://www.myiem.org.my/